2015
DOI: 10.1080/13607863.2015.1033684
|View full text |Cite
|
Sign up to set email alerts
|

Age of onset and progression of hoarding symptoms in older adults with hoarding disorder

Abstract: Objectives-We investigated (1) age of onset of hoarding disorder (HD) symptoms and diagnosis, (2) late-onset HD, (3) progression of HD symptoms, and (4) association between demographics and hoarding progression.Method-Eighty-two older adults with HD provided retrospective ratings of their hoarding symptoms for each decade of life. Age of onset of symptoms (saving, difficulty discarding, and clutter) was operationalized as the first decade in which the participant reported at least minor symptom severity, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 23 publications
2
53
0
3
Order By: Relevance
“…The onset of hoarding symptoms, whether in the context of hoarding symptoms or HD, is most likely to occur prior to age 20 years [36,38,40] , which is consistent with the typical age of onset of OCD [41] . However, in contrast to the typical cyclical course of OCD symptoms across the lifespan [42] , hoarding symptoms are likely to be chronic [36] and progressive over the lifespan [36,40,43] . One recent study indicated that the prevalence of provisional HD diagnoses increased steadily by 20% with every 5 years of age [43] .…”
Section: Agementioning
confidence: 65%
See 2 more Smart Citations
“…The onset of hoarding symptoms, whether in the context of hoarding symptoms or HD, is most likely to occur prior to age 20 years [36,38,40] , which is consistent with the typical age of onset of OCD [41] . However, in contrast to the typical cyclical course of OCD symptoms across the lifespan [42] , hoarding symptoms are likely to be chronic [36] and progressive over the lifespan [36,40,43] . One recent study indicated that the prevalence of provisional HD diagnoses increased steadily by 20% with every 5 years of age [43] .…”
Section: Agementioning
confidence: 65%
“…Instead, extant research into the age of onset of HD is reliant on retrospective data [36,38,40] and only one study [40] used a sample of participants meeting DSM-5 criteria for HD. The onset of hoarding symptoms, whether in the context of hoarding symptoms or HD, is most likely to occur prior to age 20 years [36,38,40] , which is consistent with the typical age of onset of OCD [41] .…”
Section: Agementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, for some, pathological hoarding behaviours have a later onset and are associated with stress or loss (Grisham et al, 2006). Approximately a quarter report onset of hoarding disorder after the age of 40 (Dozier, Porter & Ayers, 2016). Loss, for example loss of career, through retirement, or loss of a spouse may be more likely to occur as people get older.…”
Section: Discussionmentioning
confidence: 99%
“…9,24,37,38 Quando o TA é subdividido em seus sintomas principais de entulhamento, aquisição e difi culdade em descartar, a aquisição (seja através de compra, coleta ou mesmo furto) parece iniciar-se mais tardiamente do que os outros sintomas. Uma possível explicação é a maior independência física e fi nanceira dos indivíduos ao alcançarem a idade adulta.…”
Section: Características Clínicasunclassified